Prospects for carbon-neutral maritime fuels production in Brazil. (1st December 2021) - Carvalho, Francielle; Müller-Casseres, Eduardo; Poggio, Matheus; Nogueira, Tainan; Fonte, Clarissa; Wei, Huang Ken; Portugal-Pereira, Joana; Rochedo, Pedro R.R.; Szklo, Alexandre; Schaeffer, Roberto
Abstract: The International Maritime Organization (IMO) has compromised to reduce its greenhouse gas (GHG) emissions in the mid- and long-terms. Besides energy efficiency measures, the development of potentially carbon neutral fuels in the upcoming years is key to achieve the sector's goals. Brazil is a major commodity exporter whose unfavored geographical position increases the carbon intensity of its maritime transportation. In this context, this study presents a multicriteria methodology to compare possible alternative fuels for the Brazilian maritime trade. To this end, 14 fuel options are evaluated according to technical, economic, and environmental criteria to which different weights are assigned. The ranking of results indicates that drop-in fuels such as Fischer-Tropsch diesel, alcohol-based diesel, straight and hydrotreated vegetable oils and e-diesel stand out as promising mid-term alternatives. Biomass-based liquefied natural gas (Bio-LNG) performance in the evaluation is hampered mostly by the risk of methane slip. Green hydrogen and green ammonia, on the other hand, seem to be less competitive alternatives in the mid-term horizon for Brazil but may become alternatives for cabotage transport in the long-term. Highlights: Distilled biofuels seem to be the most promising alternative fuels in Brazil. Bio-LNG may not be suitable for long-distance maritime transport. Green H2 is penalized by costs, energy density and applicability disadvantages. Green ammonia may be an alternative for Brazilian cabotage transport. E-fuels face significant challenges in terms of cost and technological maturity.